The extermination of the European Jews - Gerlach, Christian 1963- (New approaches to European history, 2016)
"This major reinterpretation of the Holocaust surveys the destruction of the European Jews within the broader context of Nazi violence against other victim groups. Christian Gerlach offers a unique social history of mass violence which reveals why particular groups were persecuted and what it was that connected the fate of these groups and the policies against them. He explores the diverse ideological, political and economic motivations which lay behind the murder of the Jews and charts the changing dynamics of persecution during the course of the war. The book brings together both German actions and those of non-German states and societies, shedding new light on the different groups and vested interests involved and their role in the persecution of non-Jews as well. Ranging across continental Europe, it reveals that popular notions of race were often more important in shaping persecution than scientific racism or Nazi dogma"--